Eating disorders sourcebook : basic consumer health information about anorexia nervosa, bulimia nervosa, binge eating disorder, orthorexia, and other eating disorders and related concerns, such as compulsive exercise, female athlete triad, and body dysmorphic disorder, including details about risk factors, warning signs, media influence, adverse health effects, methods of prevention, treatment options, and the recovery process ; along with suggestions for maintaining a healthy weight, improving self-esteem, and promoting a positive body image, a glossary of related terms, and a directory of resources for more information. - Omnigraphics, Inc. (Detroit, MI : Omnigraphics, Inc., 2016)
"Provides basic consumer health information about risk factors, causes, complications, recovery from, and prevention and treatment of various eating disorders. Includes index, glossary of related terms, and other resources"--
Includes bibliographical references and index.
Keywords: Eating disorders; Consumer education